PELATIHAN PEMBUATAN TEMPE TURIS (Cajanus Cajan L) BAGI MASYARAKAT KELOMPOK TANI SEHATI DESA TUBLOPO, KABUPATEN TIMOR TENGAH UTARA - Risna Erni Yati Adu; Yuni Sine; Emilia Juliyanti Bria; Elisabeth Korbafo; Hermina Manlea; Dicky Frengky Hanas; Lukas Pardosi (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The training on tempeh fermentation from pigeon pea was carried out by a lecturer team from Timor University to the people of Tublopo Village (Sehati Farmer Group). Tublopo Village has one of the natural resources that potentially to be developed, namely Pigeon pea. The lack of knowledge and skills of the local community in processing the abundant pigeon pea is the reason for conducting this activity. Training on pigeon pea processing into tempeh can improve the selling value of the product and produce products with new innovations that have better quality. The used method in this service activity is in the form of counseling and the practice of making pigeon pea tempeh. At the counseling stage, the service team described the employed materials, tools and the steps for tempeh fermentation, then continued with a demonstration of making tempe according to the described stages. The main product from this service is pigeon pea tempeh. In addition to tempe products, members of the Sehati Farmer Group have been equipped with the knowledge and skills to produce tempe independently.